ANALISIS PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA PT. TUNAS INDONESIA TOURS and TRAVEL CABANG YOGYAKARTA) - Yunita Prihastuti; Endang Widayati (STIE Pariwisata API Yogyakarta, 2019)
This study aims to determine the effect of marketing mix on purchasing decisions at PT. Tunas Indonesia Tours and Travel Yogyakarta branch. Marketing mix variables consist of 4 sub variables namely: Price (X1), Product (X2), Promotion (X3), and Place (X4). The population in this study is consumers who make purchases at PT. Tunas Tours and Travel Yogyakarta in 2016. Using non-random sampling method with purposive sampling technique with a sample of 100 respondents. In this study using is descriptive and quantitative using multiple linear regression method. The results showed that price and location or distribution variables have a positive and significant influence on purchasing decisions. This is shown from the results of multiple linear regression test where both variables have P value less this of 5% and t arithmetic is greater t table. While the product and promotion variables have an insignificant effect on purchasing decisions. This is shown from the results of multiple linear regression test of these variables have a value of P value is greater of 5% significant. The test results simultaneously, show the marketing mix has a significant influence in purchasing decisions where the test results proved P value less this of 0.05 or 5%Keywords: product, price, place, promotion, purchasing decision